استخدام تمرينات باسلوب التدريب الدائري لتطوير القوة المميزة بالسرعة وتأثيرها في تحسين المستوى الرقمي لركض 200متر الطالبات - ميرز, طارق أحمد; حامد, رشا رائد (Sulaimani Journal for Humanities, 2018)
The purpose of the research is preparing exercises in the circular training to develop powerful speed and its impact in development the level of 200 running meters female students identifying the impact of these exercises by using circular training method to develop powerful speed and its impact in development level of 200 running meters of female students the sample of the research intentionally has been selected from third stage female students- Physical Education School/ Basic Education Department/ Sulaimani University 2016-2017, and they represent the sample of the research they are two groups (A,B), group (A) selected by lot to be controlled group, and group (B) to be experimental group, training program of the experimental group contains (16) training units, (2) training units per week, for 2 months, by high load degree, the researcher depended on increased training load method, and suitable statistical indications has been used, the researcher reached the following conclusions using circular training method has its impact in development the level of 200 running for female students the researcher recommended using this method for its impact in development physical side to stay away from traditional methods while using circular training method prefer using high intensity prolonged training for its impact in development different sides.